TRIZ-Based Approach in Capturing and Managing Indigenous Innovation and Knowledge - Timothy George, Mintu; Narayanan, Kulathuramaiyer; Franklin, George; John, Phoa Chui Leong (Springer Nature Switzerland, 2022)
Indigenous people who are still connected to traditional lifestyles and are living closely in touch with nature’s patents, remain custodians to vast treasures of knowledge. The ability to tap on indigenous inventions can be useful within a contemporary context in providing insights to help solve emergent problems such as global warming and climate change. This research focuses on exploring ways to capture this implicit and tacitly held knowledge among these remote indigenous communities of Sarawak, Borneo. Engaging with the local community in exploring the immense challenge requires a participatory model for eliciting innovative expressions across time and space boundaries. Mechanisms to associate such discovered knowledge within the context of current scenarios requires a standard framework for achieving the alignment. In this paper, a TRIZ-based framework for connecting to and mapping these past innovations has been proposed. The 40 inventive principles of Genrich Altshuler has been adopted as a means of bridging knowledge gaps and connecting the diverse knowledge forms. The collection of customized TRIZ instruments served as a collaborative visual knowledge mapping framework for acquiring and organizing knowledge for local indigenous communities. This study has demonstrated the ability to unlock tacit knowledge amongst community knowledge-custodians living in remote and isolated communities. The 40 Inventive Principles served not only as an index for innovative expressions but also as a good platform for these communities to make systems innovation as a way of life, and also to acquire expertise from external sources. The continuing efforts in knowledge-based activities has a potential for expansion to be used by other communities. Despite the initial challenges where there was a need to address language and intergenerational gaps, the proposed model has also demonstrated interest amongst youths to connect to their roots and share the past inventive moments with community elders.